Information technology and the productivity paradox assessing the value of investing in IT - Lucas, Henry C. (Oxford Univ. Press, 1999)
As firms push rapidly into the business world of the 21st Century, the question has remained: how do firms measure returns from substantial investments in IT
Keywords: Informatietechnologie; Investeringen; Investimentos; Return on investment; Tecnologia da informação (aspectos econômicos); Capital investments; Information technology -- Finance; Rate of return; Rentabilität; Informationstechnik; Finanzinvestition